2019
DOI: 10.1002/ijc.32692
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA TC0101441 induces epithelial–mesenchymal transition in epithelial ovarian cancer metastasis by downregulating KiSS1

Abstract: Peritoneal metastasis is a critical feature and clinical challenge in epithelial ovarian cancer (EOC). We previously identified a novel long noncoding RNA (lncRNA, TC0101441) in epithelial ovarian cancer (EOC) using microarrays. However, the impact of TC0101441 on EOC metastasis and prognosis remains unclear. TC0101441 expression in EOC tissues and its correlation with clinicopathological factors and prognosis were examined. A series of in vitro and in vivo assays were performed to elucidate the roles and mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Chemotherapy is widely used for treating locally advanced and metastatic OC in clinical settings; however, chemoresistance is inevitable during the long course of treatment, with the 5 years survival rate of OC patients limited to 40% ( Jiang et al, 2019 ). Due to lack of sensitive approaches for early diagnosis and the prevention of resistance to chemotherapy, most patients eventually succumb to recurrent, progressive cancers ( Qiu et al, 2019 ; Yang Y. et al, 2019 ). In consequence, the prevention, diagnosis and treatment may benefit from deeper knowledge of molecular mechanisms involved in ovarian carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy is widely used for treating locally advanced and metastatic OC in clinical settings; however, chemoresistance is inevitable during the long course of treatment, with the 5 years survival rate of OC patients limited to 40% ( Jiang et al, 2019 ). Due to lack of sensitive approaches for early diagnosis and the prevention of resistance to chemotherapy, most patients eventually succumb to recurrent, progressive cancers ( Qiu et al, 2019 ; Yang Y. et al, 2019 ). In consequence, the prevention, diagnosis and treatment may benefit from deeper knowledge of molecular mechanisms involved in ovarian carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies performed by different scientists have revealed the critical roles of lncRNAs in the oncogenicity of EOC. For instance, NORAD (31), LINC00673 (32) and Tc0101441 (33) were upregulated in EOc and have been identified as tumour promoters. Conversely, the low expression of WDFY3-AS2 (34), MAGI2-AS3 (35) and AOC4P (36) in EOc resulted in anti-tumourigenic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies performed by different scientists have revealed the critical roles of lncRNAs in the oncogenicity of EOC. For instance, NORAD [27], LINC00673 [28] and TC0101441 [29] are upregulated in EOC and identi ed as tumour promoters. In contrast, low expression of WDFY3-AS2 [30], MAGI2-AS3 [31] and AOC4P [32] in EOC results in antitumorigenic effects.…”
Section: Discussionmentioning
confidence: 99%